USING FLASHCARDS TO IMPROVE RUMAH CITTA LABSCHOOL STUDENTS’ VOCABULARY - Elizabeth Atyasanti Sekar Wening (English Language Education Study Program Association (ELESPA) or Asosiasi Program Studi Pendidikan Bahasa Inggris (APSPBI), Indonesia, 2017)
Vocabulary plays an important role in learning English. Improving vocabulary especially for children is needed to prepare them for their future. There is a media named flashcards that can be used to learn English for children and make the learning process more fun. This research aims to know how flashcards improve Rumah Citta Labschool students’ vocabulary. There are two research questions: 1) How are flashcards implemented to improve Rumah Citta Labschool students’ vocabulary? and 2) How do flashcards improve Rumah Citta Labschool students’ vocabulary? The researcher used Classroom Action Research as the methodology. In this research, there were seven participants. They were five students of English Club and two educators who were chosen by the school as the collaborators to avoid bias. In order to collect the data, the researcher used some instruments; they were field note observation, pre-test and post-test. The data of this research were in the form of qualitative and quantitative. Qualitative data were taken from the observation result and quantitative data were taken from the pre-test and post-test results. There was an increase in the average score from the pre-test to the posttest. It showed that using flashcards has really improved Rumah Citta Labschool students’ vocabulary.